2006
DOI: 10.1016/j.cub.2006.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Timing in Free-Living Rufous Hummingbirds, Selasphorus rufus

Abstract: Animals organize their lives around circannual and circadian rhythms, but little is known of their use of much shorter intervals. In the laboratory, some animals can learn the specific duration (seconds or minutes) between periods of food access. It has been supposed that wild nectarivores, such as hummingbirds, might also learn short time intervals so as to avoid revisiting emptied flowers until the nectar has been replenished. We provided free-living, territorial rufous hummingbirds each with eight artificia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
95
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 27 publications
6
95
1
1
Order By: Relevance
“…As we did not know how long it would take for a bird to learn the refill rates (if at all), we presented each of three territorial birds with an eight-flower array for 11 days. It turned out that the birds had, in fact, learned the refill rates quite well by the end of the first day (our expectations of their performance vastly underestimated their abilities) but the key finding was that all three birds returned to the 10-minute refilling flowers at around 10 minutes and to the 20-minute refilling flowers at around 20 minutes (Henderson et al, 2006a). Although these time periods are much shorter than typical refilling times for real flowers and birds may defend up to a couple of thousand flowers in their territories, we considered that the Henderson et al (2006a) data at least showed 'proof of principle' and that these birds could learn refill rates, for multiple flowers and relatively quickly.…”
Section: Figure 3 Photographs Showing the Elevated Feeder (To Deter mentioning
confidence: 82%
See 3 more Smart Citations
“…As we did not know how long it would take for a bird to learn the refill rates (if at all), we presented each of three territorial birds with an eight-flower array for 11 days. It turned out that the birds had, in fact, learned the refill rates quite well by the end of the first day (our expectations of their performance vastly underestimated their abilities) but the key finding was that all three birds returned to the 10-minute refilling flowers at around 10 minutes and to the 20-minute refilling flowers at around 20 minutes (Henderson et al, 2006a). Although these time periods are much shorter than typical refilling times for real flowers and birds may defend up to a couple of thousand flowers in their territories, we considered that the Henderson et al (2006a) data at least showed 'proof of principle' and that these birds could learn refill rates, for multiple flowers and relatively quickly.…”
Section: Figure 3 Photographs Showing the Elevated Feeder (To Deter mentioning
confidence: 82%
“…It turned out that the birds had, in fact, learned the refill rates quite well by the end of the first day (our expectations of their performance vastly underestimated their abilities) but the key finding was that all three birds returned to the 10-minute refilling flowers at around 10 minutes and to the 20-minute refilling flowers at around 20 minutes (Henderson et al, 2006a). Although these time periods are much shorter than typical refilling times for real flowers and birds may defend up to a couple of thousand flowers in their territories, we considered that the Henderson et al (2006a) data at least showed 'proof of principle' and that these birds could learn refill rates, for multiple flowers and relatively quickly. Furthermore, not only were the duration of the refill rates longer and the number of flowers that the birds could track more than has been tested in the laboratory, all of the birds were living a very active life throughout their foraging on the array, defending their territory from intruding males and displaying to females.…”
Section: Figure 3 Photographs Showing the Elevated Feeder (To Deter mentioning
confidence: 82%
See 2 more Smart Citations
“…Interval timing-sensitivity to elapsing durations-is thought to function in many different contexts, including communication (von Frisch 1967;Seeley & Tovey 1994), navigation (Srinivasan et al 2000) and foraging (Stephens & Krebs 1986;Gill 1988;Gallistel 1990;Seeley & Tovey 1994;Clayton & Dickinson 1998;Ohashi 2002;Henderson et al 2006). Interval timing ability is known to occur in several vertebrates, including humans (Richelle & Lejeune 1980;Lejeune & Wearden 1991), and was recently discovered in bumble-bees, Bombus impatiens (Boisvert & Sherry 2006).…”
Section: Introductionmentioning
confidence: 99%